Viral Marketing: A New Branding Strategy to Influence Consumers - Yang, Xiaofang (Université d'Ottawa / University of Ottawa, 2012)
The rapid penetration of the Internet and the prevalence of various social media facilitated by new technologies provide new opportunities for how marketing techniques are developed and refined. The creation of viral marketing has been driven by technological innovations and cultural changes. Responding to marketing trends and catering to consumers’ psychological demands and behavioral changes, viral marketing represents the latest online customer-centric marketing (Shukla, 2010). Extending the advertising effects of word-of-mouth (WOM) communication and Internet marketing, viral marketing has demonstrated considerable success and utility in a promotional phase and development process of a product and/or service. This study intends to illustrate the benefits and challenges of viral marketing. The effects and concerns with the adoption of viral marketing are reinforced by previous research and findings from marketer and consumer focus groups. This thesis will contribute to building a theoretical and empirical foundation for viral marketing research and professional practice.
Keywords: Viral Marketing; electronic Word-of-Mouth Communication (eWOM); Internet Marketing; New Media